Pore types and microstructure of the black shale in the Lower Silurian, Southeast of Chongqing, China - Li, Juan; Tian, Yukun; Chen, Shan; Zhou, Hui; Chi, Huanpeng; Ma, Yanyan; Kong, Liyun (Frontiers in Earth Science, 2023)
The Lower Silurian black shale in the Southeast of Chongqing is of great potential in the accumulation of shale gas in South China. In order to understand the pore system of these black shales, mercury porosimetry, surface area study, mineralogy and image analyses by scanning electronic microscopy were performed. Four major pore types (interparticle pores, intraparticle pores, organic-matter pores and microfractures) were classified under the observation of the samples. Interparticle pores, which associate with mineral particles and mostly in micro-scale, can be subdivided into pores among rigid particles, ductile particles, and rigid-ductile particles. Intraparticle pores, which can be subdivided into cleavage-plane pores within clay minerals, intercrystalline pores within pyrite framboids and pores formed by partial or complete dissolution, are in nanometer scale and more common exist in unweathered rocks. Organic-matter pores are one type of intraparticle pores which are found within organic matter and appear to be prone to form effective networks and main permeable pathway. The rocks are abundant with microfractures where absorbed gas can be transformed to free gas. Microfractures which are partly cemented by residual organic residue are of great importance. Comparing the two sets of samples from Lujiao section and Well Yuye-1, we note that the outcrop samples from Lujiao section have much more interparticle pores than core samples, while the latter own more intraparticle pores. The results of quantitative and visual qualitative analyses about the gas shale reservoir pore system are similar. With the increasing of quartz, the number of interparticle pores and macropores increase. And intraparticle pores and micro-mesopores increase with clay minerals.